Schaum's Outlines Statistics - SPIEGEL ([S.l.] : Tata McGraw-Hill, 2010)
This book is designed for use as a supplement to all current standard texts or as a textbook for a formal course on statistics. It should also be of considerable value to those taking courses in mathematics, management, commerce, or any of the numerous other fields in which statistical methods are employed.
Keywords: Statistical mathematics